Effect of Secondary Education on Cognitive and Non-cognitive Skills - Jani-Petteri Ollikainen; Tuomas Pekkarinen; Roope Uusitalo; Hanna Virtanen (Institute of Labor Economics (IZA), 2022)
We exploit admission cutoffs to secondary schools to study the effects of general academically oriented, versus vocational secondary schooling on cognitive and non-cognitive skills using a regression discontinuity design. We measure these skills using the Finnish Defence Forces Basic Skills Test that due to compulsory military service covers the vast majority of Finnish men and is a strong predictor of later labor market success. We find that large differences in average skills across students that differ in their schooling when entering military service are due to selection rather than causal effects of secondary schooling on either cognitive or non-cognitive skills.
Keywords: J24; I21; 330; non-cognitive skills; regression discontinuity; secondary schooling